A Model for Scaffolding Academic IELTS Writing Task 2: MMPIPE - Ince Dian Aprilyani Azir (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
The study uses the theory of scaffolding and ZPD (Vygotsky, 1978) as the guidelines to explain in what ways scaffolding can help the teacher to improve the EFL students’academic writing. To make it easier, the author formulates the scaffolding-based activity namely MMPIPE. It stands for Motivating, Modelling, Peer Brainstorming, Independent Writing, Peer Feedback, and Evaluation which are elaborated within theories of sociocultural framework. The model of MMPIPE scaffolding was used at the one-week Intensive Classes for IELTS Writing in Jakarta, Indonesia.The classes were for the EFL learners aged varied between 18 up to 28 years old coming from various backgrounds who want to continue studying at English speaking countries. The past results of applying the MMPIPE scaffolding writing have shown that the learners achieve the optimal Zone Proximal Development by successfully gaining the increased score band between 0.5 and 1.5 band scale. However, the MMPIPE model also has some limitations in ways that it may lead to the different results if the activity uses the different material sources. Furthermore, due to some considerations, it is only applicable to intermediate up to advanced level.